Graphene : properties, preparation, characterisation and devices - Skakalova, Viera; Kaiser, Alan B. (Woodhead Publishing series in electronic and optical materials ;, 2014)
Graphene: Properties, Preparation, Characterisation and Devices reviews the preparation and properties of this exciting material. Graphene is a single-atom-thick sheet of carbon with properties, such as the ability to conduct light and electrons, which could make it potentially suitable for a variety of devices and applications, including electronics, sensors, and photonics. Chapters in part one explore the preparation of, including epitaxial growth of graphene on silicon carbide, chemical vapor deposition (CVD) growth of graphene films, chemically derived graphene, and graphene produced by electrochemical exfoliation. Part two focuses on the characterization of graphene using techniques including transmission electron microscopy (TEM), scanning tunneling microscopy (STM), and Raman spectroscopy. These chapters also discuss photoemission of low dimensional carbon systems. Finally, chapters in part three discuss electronic transport properties of graphene and graphene devices. This part highlights electronic transport in bilayer graphene, single charge transport, and the effect of adsorbents on electronic transport in graphene. It also explores graphene spintronics and nano-electro-mechanics (NEMS). Graphene is a comprehensive resource for academics, materials scientists, and electrical engineers working in the microelectronics and optoelectronics industries. Explores the grapheme preparation techniques, including epitaxial growth on silicon carbide, chemical vapor deposition (CVD), chemical derivation, and electrochemical exfoliation. Focuses on the characterization of graphene using transmission electron microscopy (TEM), scanning tunneling microscopy (STM), and Raman spectroscopy. A comprehensive resource for academics, materials scientists, and electrical engineers.